Local Discrimination in Transportation - Ripley, W. Z. (Quarterly Journal of Economics, 1909)
Examples of anomalies, 470.—Hadley's oyster case not conclusive, 472.—Two variants: lower long-haul rates by the roundabout route, as in the Hillsdale, Youngstown, and some Southern cases, 474; or by the direct route, as in the Nashville-Chattanooga and other Southern cases, 480.—Complicating influence of water transportation, 488.—Market competition from various regions a different case, 489.—The basing point (Southern) and basing line (Missouri River) systems, 494.—Their inevitable instability and probable ultimate abandonment, 498.—Postage-stamp rates, illustrated by transcontinental tariffs, 499.